The Contributions of Arab Muslim in the Astronomical Geography - Ali, Sahmy khidher (Journal of Tikrit University for Humanities, 2023)
The works of Arab Muslim geographers have made significant contributions to the study of Astronomy, resulting in a substantial increase in their understanding of celestial phenomena and its broader implications for geography. Consequently, the significance of these contributions became evident in the advancement of geographical philosophy and the field of astronomical geography. Prior to the advent of Islam, the Arab civilization had a profound interest in celestial phenomena, including the sky, stars, and planets. They adeptly used the knowledge derived from observing the positions of celestial bodies to navigate and orient themselves throughout their journeys. However, the emergence and subsequent expansion of Islam led to a significant advancement in the field of Astronomy. This progress was accompanied by the development of many devices and instruments, including Astrolabes, Sundials, Azimuths, Strings, several kinds of compasses, as well as the notable inventions of the great and tiny Ring.The individual’s desire and ambition to acquire knowledge about astronomical subjects grew as a result of its connection to the fundamental principles of Islam, including prayer, fasting, and pilgrimage. These responsibilities are associated with specific time periods. Hence, the determination of both the time and direction of Qibla is exclusively reliant on celestial bodies.